Tantra in Pynchon's Against the Day. Issue 3 (27th May 2017) - Rothfork, John
ABSTRACT: Pynchon's Against the Day seems to be a historical novel describing the struggle between capitalism and anarchy in the Gilded Age. However, the antagonists, Scarsdale Vibe and Webb Traverse, perish without successors. The view from the dirigible, Inconvenience, symbolizes Buddhist detachment from the battle ( maya ), which is elaborated by allusions to Tantra. The Trespasser, Ryder Thorn, preaches a social gospel to condemn the Chums of Chance for their dreamy detachment (p. 551). But the end of the novel endorses the Chums and the Tantric promise of the Inconvenience that floats above a violent world.